The effect of capital structure on profitability food and beverage sub sector manufacturing companies listed on the Indonesia Stock Exchange, 2018-2021 - Ulfa Yanti; Anita Munir (President University, 2021)
This study aims to determine whether there is a relationship or influence of capital structure on profitability. A total of 14 manufacturing companies in the food and beverage sub-sector were sampled in this study using a purposive sampling technique. SPSS version 25 program becomes a tool for data analysis using multiple linear regression models. Capital structure is the independent variable in this study as measured by the Debt to Equity Ratio, Debt to Asset Ratio and Long Term Debt to Equity Ratio. Meanwhile, profitability in this study is the dependent variable as measured by Return on Equity. The standard level of significance in this study is 5%, so the results in this study, simultaneously capital structure has a significant effect on profitability while partially DER has a significant positive effect on ROE, DAR and LDER have a significant negative effect on ROE.